Unveiling a new taxonomy in education field - Muhamad Afzamiman, Aripin; Rohana, Hamzah; P., Setya; M. H. M., Hisham; M. I., Mohd Ishar (Institute of Advanced Engineering and Science, 2020)
Taxonomy is a set of hierarchical models that is applied to classify educational learning goals or objectives into a certain level of complexity. Many models have been developed and implemented to suit the educational settings of schools or educational institutions around the world. Realising the importance of educational taxonomy, the purpose of this paper is to explore the function and role of the taxonomy framework used in education, especially through the lens of Bloom, Anderson and SOLO’s (Structure of the Observed Learning Outcome) framework. In addition, this concept paper also aims to formulate a more holistic alternative taxonomy based on the concept of Syed Muhammad Naquib Al-Attas. Research on Bloom, Anderson and SOLO’s taxonomies is not intended to deny the role and contribution of existing taxonomies, but to provide an alternative and space in creating a balanced system of cognitive classification of students through teaching and learning as well as in the evaluation system.